a^4+5a^2b^2+9b^4 4a^4+24a^2b^2+25b^4
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 14:06:55
a^4+5a^2b^2+9b^44a^4+24a^2b^2+25b^4a^4+5a^2b^2+9b^44a^4+24a^2b^2+25b^4a^4+5a^2b^2+9b^44a^4+24a^2b^2+
a^4+5a^2b^2+9b^4 4a^4+24a^2b^2+25b^4
a^4+5a^2b^2+9b^4 4a^4+24a^2b^2+25b^4
a^4+5a^2b^2+9b^4 4a^4+24a^2b^2+25b^4
a^4+5a^2b^2+9b^4
=a^4+6a²b²+9b^4-a²b²
=(a²+3b²)²-a²b²
=(a²+ab+3b²)(a²-ab+3b²)
4a^4+24a^2b^2+25b^4
=4a^4+24a²b²+36b^4-11b^4
=(2a²+6b²)²-11b^4
=[2a²+(6+√11)b²][2a²+(6-√11)b²]
2(a+b)-[4(a+b)-3(a+b)]一[5(a-b)+(a-b)]过程
a-b/a+b=4,求代数式5(a-b)/a+b-a+b/2(a-b)的值.
若a-b/a+b=4,求5a-b/a+b- a+b/2(a-b)
若a-b/a+b=4,求代数式5(a-b)/a+b-a+b/2(a-b)
计算:((a+b)(a-b)-(a-b)^2+2b(a-b))/4(a-b)
等式:(a+b)^0=1 (a+b)^1=a+b (a+b)^2(a+b)^0=1(a+b)^1=a+b(a+b)^2=a^2+2ab+b^2(a+b)^3=a^3+3a^2b+3ab^2+b^3问:(a+b)^4=?(a+b)^5=?``````` (a+b)^9=?
a+a-a+2a-3a-2b+3b-5b+3b-4b-5b
计算a^2-b^2/a+b-4a(a-b)+b^2/2a-b
已知a*a+b*b-2a+4b+5=0,求2(a+b)(a-b)+(a-b)(a-b)-(6a*a*b-2a*b*b)/(2b)的值
(a-b)(a^5+a^4b+a^3b^2+ab^4+b^5)bggg
1/4(a-b)^2+3(a-b)(a+b)+9(a+b)^2
化简8(a-b)2+4(a-b)+5(b-a)-6(b-a)2
[(a+b)^-3(a-b)^5/(a-b)^-2(a+b)^4]^2怎么写
已知a+b+4a-2b+5=0 求a-b分之a+b
a*a+b*b-2a+4b+5=0 求a-b
5(a-b)-4(a+b)-3(a-b)+2(a+b)怎么算?
(a-b)^2*(b-a)^5+(b-a)^3*(a-b)^4=?
2a+(4a-5b)-3(a-2b)